Tautomerizable β-ketonitrile copolymers for bone tissue engineering: Studies of biocompatibility and cytotoxicity - Lastra, María Laura (2015)
β-Ketonitrile tautomeric copolymers have demonstrated tunable hydrophilicity/hydrophobicity properties according to surrounding environment, and mechanical properties similar to those of human bone tissue. Both characteristic properties make them promising candidates as biomaterials for bone tissue engineering. Based on this knowledge we have designed two scaffolds based on β-ketonitrile tautomeric copolymers which differ in chemical composition and surface morphology. Two of them were nanostructured, using an anodized aluminum oxide (AAO) template, and the other two obtained by solvent casting methodology. They were used to evaluate the effect of the composition and their structural modifications on the biocompatibility, cytotoxicity and degradation properties. Our results showed that the nanostructured scaffolds exhibited higher degradation rate by macrophages than casted scaffolds (6 and 2.5% of degradation for nanostructured and casted scaffolds, respectively), a degradation rate compatible with bone regeneration times. We also demonstrated that the β-ketonitrile tautomeric based scaffolds supported osteoblastic cell proliferation and differentiation without cytotoxic effects, suggesting that these biomaterials could be useful in the bone tissue engineering field.